Habitat preference in the critically endangered yellow‐tailed woolly monkey (Lagothrix flavicauda) at La Esperanza, Peru. Issue 8 (18th July 2019) - Almeyda Zambrano, Sandra L.; Broadbent, Eben N.; Shanee, Sam; Shanee, Noga; Deluycker, Anneke; Steinberg, Michael; Ford, Scott A.; Hernández Jaramillo, Alma; Fernandez‐Hilario, Robin; Lagos Castillo, Carolina; Almeyda Zambrano, Angelica M.
Abstract: Habitat loss is one of the main threats to wildlife. Therefore, knowledge of habitat use and preference is essential for the design of conservation strategies and identification of priority sites for the protection of endangered species. The yellow‐tailed woolly monkey ( Lagothrix flavicauda Humboldt, 1812), categorized as Critically Endangered on the IUCN Red List, is endemic to montane forests in northern Peru where its habitat is greatly threatened. We assessed how habitat use and preference in L. flavicauda are linked to forest structure and composition. The study took place near La Esperanza, in the Amazonas region, Peru. Our objective was to identify characteristics of habitat most utilized by L. flavicauda to provide information that will be useful for the selection of priority sites for conservation measures. Using presence records collected from May 2013 to February 2014 for one group of L. flavicauda, we classified the study site into three different use zones: low‐use, medium‐use, and high‐use. We assessed forest structure and composition for all use zones using 0.1 ha Gentry vegetation transects. Results show high levels of variation in plant species composition across the three use zones. Plants used as food resources had considerably greater density, dominance, and ecological importance in high‐use zones. High‐use zones presented similar structure to medium‐ and low‐use zones; thus it remains difficult to assess the influence of forest structure on habitat preference. We recommend focusing conservation efforts on areas with a similar floristic composition to the high‐use zones recorded in this study and suggest utilizing key alimentation species for reforestation efforts. Abstract : This adult male of yellow‐tailed woolly monkey, (Lagothrix flavicauda) was photographed at our study site in Amazonas region, Peru. Photo by Neotropical Primate Conservation Research Highlights: Forest composition is more important than forest structure for Lagothrix flavicauda habitat preference in the northern Peruvian Andes. Zones highly used by L. flavicauda in the study site show similar floristic composition and natural regeneration of feeding plants.